Leadership Style's influence on workforce productivity - Ardiansyah Halim (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The objective of this study is to analyze and examine instructive, consultative, participatory and delegative leadership styles on the productivity of employee work. This study, with a population and a sample of 32 individuals, was conducted at Bank Danamon Savings and Loan Unit Pinrang. Descriptive and multiple linear regression analysis is the data analysis used. The results of the study show that at the Bank Danamon Savings and Loans and Loan Units, the instructive leadership style does not have a significant impact on employee work productivity. Employee productivity at the Bank Danamon Savings and Loans and Loan Units is not significantly affected by the advisory leadership style. At Bank Danamon Savings and Loans and Loan Units, the participatory leadership style has a significant impact on employee productivity. The style of delegate leadership at Bank Danamon Savings and Loans Unit Pinrang has a significant impact on employee work productivity. Delegative leadership style is the variable that at Bank Danamon Savings and Loans and Loan Units has the most dominant influence on employee work productivity.